A descriptive study of the use of cardiac point of care ultrasound (PoCUS) in public emergency centres in Cape Town - Ganas, Ushira (Department of Medicine, 2022)
Background Cardiac point of care ultrasound (PoCUS) has evolved into an important diagnostic tool in the daily practice of emergency medicine. Its use has been advocated internationally, but its limitations have also been emphasised. The indications for cardiac PoCUS vary somewhat in different parts of the world, and training programs may also differ. We set out to describe the self-reported indications and imaging windows used at a selection of secondary-level, public hospital emergency centres in Cape Town. Methods A descriptive study with prospective data collection from the emergency centres of Mitchells Plain District, Victoria and New Somerset Hospitals was used. Data were collected over a three-month period, by all formally consented providers who have completed a basic emergency ultrasound course, using a purpose-designed data collection tool for all cardiac PoCUS scans. The study was approved the University of Cape Town's Human Research Ethics Committee (581/2017). Results We recruited 15 PoCUS providers who recorded 267 data entries over the 3-month study period. Seventeen surveys were excluded leaving 250 for analysis. The most common indication for cardiac PoCUS was electrocardiogram abnormalities,27% (n= 112); dyspnoea,25% (n= 102); chest pain,16%(n=65); cardiomegaly on chest xray,12%(n=51); new murmur,6%(n=23); and chest trauma,5%(n=22). Other indications made up the remaining 10%(n=40). Parasternal long and short axis were the predominantly used views. Conclusion The results of the study suggest that cardiac PoCUS is used for a wide range of indications which are recommended in training guidelines. However, some indications are outliers but may be useful in low-middle income settings. Further research needs to be done to ascertain the extent of the use of cardiac PoCUS, and possibly the need for a more comprehensive training program with adequate training in these clinical conditions, to ensure safe practice.